Growth of Forest Stands and Tree Species Ecological Guilds in Undisturbed and Selectively Logged Amazonian Forests, Northern Brazil - Karfakis, Theodoros. S.; Volkmer-Castilho, Carolina (International Journal of Bio-resource and Stress Management, 2023)
The growth of trees in forest canopy gaps left by the felling of adult commercial trees has been shown to differ for individual ecological guilds of tree species and initial site conditions prior to logging. The objective of this study was to identify patterns in individual tree diameter growth both for the tree population overall and as a function of ecological guild in specific for undisturbed and selectively logged forest and compare between the two. Data came from two areas of non-flooded forest of the Brazilian Amazon in the states of Amazonas and Para for trees with dbh >10 cm. For purposes of statistical analysis tree species were clustered in three ecological guilds based on bole wood specific gravity and successional status. Tree growth irrespective of ecological species guild in the vicinity of logging gaps for the three year period following the harvest event was significantly more elevated in relation to undisturbed forest and this positive difference was proportionately greater for Amazonas in relation to Para. Ecological guilds showed a pattern of increasing growth rate with decreasing bole wood specific gravity and successional status when area and site disturbance status where not taken under account. In response to logging all ecological guilds showed increased growth rates but all were proportional to levels found in the undisturbed forest. Tree species life history characteristics appear to be a more significant factor affecting tree growth than site disturbance status in response to logging at least for the first 3 years after the logging event.